Analysis of Agency Problems in Development Plan Alignment: An Indonesia-Malaysia Comparative Study - Afsdy Saksono, Rochmad Nur (Jurnal Ilmu Administrasi Negara, 2012)
Development plan alignment (local with national development plan) hasbecome importance issue for developing countries both unitary state, butalso federal state. The objectives of this paper are to compare agencyproblems faced by Indonesia and Malaysia in aligning development planand to critically review Indonesia and Malaysia policies to address suchproblems in order to ensure development plan alignment. The studyfound that the degree of agency problem in development plan alignmentplan in Indonesia is higher than that in Malaysia. The design ofdecentralization in Malaysia is more centralized than that in Indonesia,particularly in three aspects:organizational design of developmentplanning agencies, mechanism and process of development planning, andbudgeting system (inter-government financial transfer). The threeaspect/factors have significant contribution to the agency problem.